2021
DOI: 10.1111/apa.15971
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of the association between paediatric obesity and telomere length

Abstract: Paediatric obesity has become a public health problem worldwide.From 1975 to 2016, the global age-standardised prevalence of paediatric obesity has increased from 0.7% to 5.6% in girls and from 0.9% to 7.8% in boys. 1 Physical inactivity, prolonged sedentary time, unhealthy eating patterns, and an imbalanced diet containing high calories were the main drivers for the increase. 2 In children, obesity can increase the risk of various comorbidities, including type 2 diabetes, fatty liver disease, and obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In a recent systematic review and meta-analysis by Lin L et al ( Lin et al, 2021 ), a lower LTL was reported in obese children compared to non-obese ones (SMD: −0.85; 95% CI: −1.42 to −0.28; p < 0.01). However, they reported the results by fixed effects model, in which the major assumption is that the true effect is the same in all studies.…”
Section: Introductionmentioning
confidence: 94%
“…In a recent systematic review and meta-analysis by Lin L et al ( Lin et al, 2021 ), a lower LTL was reported in obese children compared to non-obese ones (SMD: −0.85; 95% CI: −1.42 to −0.28; p < 0.01). However, they reported the results by fixed effects model, in which the major assumption is that the true effect is the same in all studies.…”
Section: Introductionmentioning
confidence: 94%
“…Obesity and its comorbidities in humans are associated with increased pro- and decreased anti-oxidation, respectively, even in childhood [ 72 , 113 , 115 , 116 ]. Increased levels of oxidative stress are considered detrimental to cell signal transduction [ 117 ], potentially explaining the reported correlation between increased oxidative stress and shorter TL [ 118 , 119 , 120 ]. The adipose tissue plays a role in the production of inflammatory cytokines and chemokines, as well as in host defense, immunity, and injury response [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a significant inverse relation between the levels of inflammation and TL in both adults [ 78 ] and children [ 136 ]. In obesity, increased adipose tissue results in increased production of pro-inflammatory adipokines and cytokines [ 137 ] and potentially TL shortening [ 106 , 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Landgren comments on the findings 2 . Readers may also be interested in a systematic review and meta‐analysis by Lin et al on the association between paediatric obesity and telomere length 3 …”
Section: Stimulant Drugs Helped 43% Of Children With Adhd To Tackle W...mentioning
confidence: 99%